The effect of pH on anaerobic fermentation of primary sludge at room temperature - Wu, Haiyan; Yang, Dianhai; Zhou, Qi; Song, Zhoubing (Journal of hazardous materials, 2009)
The effect of pH in the range of 3.0–11.0 on anaerobic fermentation of primary sludge (PS) was investigated at room temperature. The experimental results showed that the concentrations of soluble chemical oxygen demands (SCOD), soluble protein and carbohydrate and short-chain fatty acids (SCFAs) under alkaline conditions were significantly higher than those under other pHs. At fermentation time of 5 days, the average SCFAs concentration increased from 968 to 3511 mg COD/L with the increase of pH from 3.0 to 10.0. However, further increasing pH to 11.0 resulted in the decrease of SCFAs. At pH 10.0, acetic, propionic and iso-valeric acids were the three main products, and the volatile suspended solids (VSS) reduction reached 38%. It was also observed that at any pH value investigated, there were obvious ammonia and phosphorus releases during fermentation. According to this study it is obvious that alkaline pH benefited the soluble organic carbon production from PS.